EVALUATION OF GENETIC DIVERGENCE IN BERSEEM (TRIFOLIUM ALEXANDRINUM L.) GERMPLASMS - D. M. LANGADE; C. N. RAM; D. N. VISHWAKARMA; SHARMA, AMITA (The Bioscan, 2013)
Forty germplasms of berseem were assessed for the nature and magnitude of genetic divergence based on ten different traits of economic importance including green forage yield per plant following Mahalanobis’s D2 statistics. The germplasms were grouped into seven clusters. The grouping showed one mono-genotypic cluster (Cluster II), while others comprised of two (Cluster IV), three (Cluster III), four (Cluster V), five (Cluster VII), nine (Cluster I) and sixteen germplasms (Cluster VI). The maximum inter-cluster distance was observed between Cluster II and IV (D2 = 51.898) and minimum between Cluster I and VI (D2 = 5.523). The maximum intra-cluster average D2 value was observed for Cluster VII (D2 = 7.354) and minimum for Cluster II (D2 = 0.000). For green and dry forage yield per plant, the maximum intra-cluster group mean was found for Cluster III (D2 = 12.65) and Cluster V (D2 = 2.41) respectively. Green forage yield per plant contributed maximum (21.45 %) and minimum contribution was through leaf: stem ratio (2.19 %) towards the total genetic divergence.